The Influence of Organizational Culture and Work Discipline on Employee Performance at PT Global Putra International Surabaya - Alfu Roshid Ubaidillah; Jimmy Ignatius; Ageng Pratiwi (Escalate : Economics and Business Journal, 2026)
Employee performance is an important factor in supporting organizational success, so a strong organizational culture and good work discipline are needed to increase productivity. This study aims to analyze the influence of organizational culture and work discipline on employee performance at PT Global Putra International Surabaya. The study used a quantitative method with an associative approach, involving all 30 employees as samples through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression analysis supported by validity, reliability, normality, multicollinearity, coefficient of determination, t-test, and F-test tests. The results showed that organizational culture and work discipline had a significant effect on employee performance, both partially and simultaneously, with a coefficient of determination of 53.6%, indicating that both variables were able to explain 53.6% of the variation in employee performance, while the rest was influenced by other factors outside the study. This study concluded that strengthening organizational culture and improving work discipline are important factors in improving employee performance. These findings provide practical implications for companies to strengthen organizational values ​​and implement work discipline consistently as an effort to improve the effectiveness of human resource management